2011
DOI: 10.1177/0954008310389202
|View full text |Cite
|
Sign up to set email alerts
|

PEBAX membranes for water desalination by pervaporation process

Abstract: Hydrophobic dense membrane PEBAX were prepared, and their suitability for a water pervaporation process was studied. The effects of the following parameters on the water flux were determined as operating conditions [brine inlet temperature (28—54°C) and NaCl concentration in the feed brine (0—3.5 mol L-1)]. A water flux of 1.3—7 g m-2 h-1 was obtained using this type of membranes. It was found that, for our application, the optimal specifications for our membrane is a thickness of 100 μm and an operating tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Hydrophobic pervaporation membranes are commonly employed for the separation of trace amounts of organic solvents from aqueous solutions. Nevertheless, the research conducted on the use of this technique in water desalination is scarce, as shown by a restricted number of papers [5,[11][12][13][14][15]. The membranes used in prior research on PV brine and seawater desalination included a PVA-based functional layer [16][17][18], a GO-based functional layer [19][20][21], an organic silica/silicate-based functional layer [22], cellulose membranes [23][24][25][26], and others [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrophobic pervaporation membranes are commonly employed for the separation of trace amounts of organic solvents from aqueous solutions. Nevertheless, the research conducted on the use of this technique in water desalination is scarce, as shown by a restricted number of papers [5,[11][12][13][14][15]. The membranes used in prior research on PV brine and seawater desalination included a PVA-based functional layer [16][17][18], a GO-based functional layer [19][20][21], an organic silica/silicate-based functional layer [22], cellulose membranes [23][24][25][26], and others [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the selection of membrane materials for gas dehydration processes [19], most membranes tested to date for PV desalination are based on hydrophilic materials to enhance the solubility component to water transport. Specifically, PV desalination studies were performed with polyether-polyamide block copolymer (PEBAX) [20][21][22], cellulose-based [23][24][25][26], polyvinyl alcohol-based (PVA) [27][28][29][30][31][32][33], graphene oxide (GO) [34][35][36], sulfonated block copolymers [37,38], ion-exchanged polyethylene [39], inorganic [40][41][42][43][44][45][46][47][48][49][50][51], and mixedmatrix/hybrid [32,[52][53][54][55]] active layers. For example, Li et al [35] synthesized a GO active layer on polyvinylidene fluoride (PVDF) support and reported a pure-water flux value of 67 kg m -² h -1 at 70 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Pervaporation (PV) has been proven to be the most promising method among various separation methods. 5,6 Various studies have been developed in butanol-water system using various membranes such as polydimethylsiloxane, 7 polyvinylidenefluoride, 8 polyurethane 9 (PU), and polyether block amide. 10 PU is one of the most widely used versatile polymers.…”
Section: Introductionmentioning
confidence: 99%